LncRNA-AC02278.4 Is a Novel Prognostic Biomarker That Promotes Tumor Growth and Metastasis in Lung Adenocarcinoma - Chen, Xi; Zhou, Fan; Ren, Wenjun; Guo, Jishu; Huang, Xiaobin; Pu, Jun; Niu, Xiaoqun; Jiang, Xiulin (Frontiers in Oncology, 2022)
LncRNA-AC02278.4 (ENSG00000248538) is a long non-coding RNA (lncRNA) found to be highly expressed in multiple human cancers including lung adenocarcinoma (LUAD). However, the underlying biological function and potential mechanisms of AC02278.4 driving the progression of LUAD remain unclear. In this study, we investigated the role of AC02278.4 in LUAD and found that AC02278.4 expression was significantly increased in datasets extracted from The Cancer Genome Atlas. Increased expression of lncRNA-AC02278.4 was correlated with advanced clinical parameters. Receiver operating characteristic (ROC) curve analysis revealed the significant diagnostic ability of AC02278.4 [area under the ROC curve (AUC) = 0.882]. In addition, gene set enrichment analysis (GSEA) enrichment showed that AC02278.4 expression was correlated with immune response-related signaling pathways. Finally, we determined that AC02278.4 regulated cell proliferation and migration of LUAD in vitro. Our clinical sample results also confirmed that AC02278.4 was highly expressed in LUAD and correlated with adverse clinical outcomes. In conclusion, our data demonstrated that AC02278.4 was correlated with progression and immune infiltration and could serve as a prognostic biomarker for LUAD.